PENERAPAN TEKNOLOGI MESIN MIXER UNTUK MENINGKATKAN KUANTITAS DAN KUALITAS PRODUK PUPUK KOMPOS DI GAPOKTAN NGUDI MAKMUR, BANJARARUM, KULON PROGO - Edhy Sutanta; Suparni Setyowati Rahayu; Raden Wisnu Nurcahyo; Samuel Kristiyana; Aris Wahyu Murdiyanto; Mukasi Wahyu Kurniawati (Universitas PGRI Yogyakarta, 2024)
The Ngudi Makmur Farmer Group (Gapoktan) is one of the productive economic groups located in Banjararum Village, Kulon Progo, Yogyakarta. Gapoktan Ngudi Makmur faces several issues, some of are deemed important and need to be resolved. The mentioned issues include environmental pollution risks and unpleasant odors arising from piles of livestock manure. Livestock manure is generally processed into compost fertilizer to nourish crops managed by the group. The process of turning livestock manure into compost fertilizer is done with the hand tool, resulted in relatively low production quantity and quality due to non-standard/uniform compost grain sizes. This Community Service Activity (PkM) is part of Kosabangsa Program implementation in 2023. The activity is carried out by a combined team from 2 (two) Higher Education Institutions (PT), namely Universitas Jenderal Achmad Yani Yogyakarta (UNJAYA), and Universitas AKPRIND Indonesia. This activity is conducted through 5 (five) stages which is: socialization, training, technology application, mentoring, as well as program evaluation and sustainability. The total duration of the activity is 4 (four) months. The appropriate technology (TTG) applied is a compost mixer machine. Based on the evaluation results after the activity, there was an increase in the quantity of compost production by 16.67% and an improvement in quality of compost with standard/uniform grain sizes. Keywords: mixer machine, quality, quantity, compost, appropriate technology